Enhanced Electrochemical Sensor for Electrocatalytic Glucose Analysis in Orange Juices and Milk by the Integration of the Electron-Withdrawing Substituents on Graphene/Glassy Carbon Electrode. (12th April 2022) - Zainul, Rahadian; Isa, Illyas Md; Akmar Mohd Yazid, Siti Nur; Hashim, Norhayati; Mohd Sharif, Sharifah Norain; Saidin, Mohamad Idris; Ahmad, Mohamad Syahrizal; Suyanta, M.Si; Amir, Yulkifli
Abstract : In this work, a novel electrochemical sensor was developed by electron-withdrawing substituent modification of 1-phenyl-3-methyl-4-(4-fluorobenzoyl)-5-pyrazolone on a graphene-modified glassy carbon electrode (HPMpFP-graphene/GCE) for glucose detection. The results of characterizations using a scanning electron microscope, Fourier transform infrared spectroscopy, Raman spectroscopy, and nuclear magnetic resonance spectroscopy showed the successful fabrication of HPMpFP-graphene nanocomposite, which served as an electroactive probe for glucose detection. The electron transfer ability of HPMpFBP-graphene/GCE has been successfully revealed using cyclic voltammetry and electrochemical impedance spectroscopy results. The good electrochemical performance was shown by well-defined peak currents of square wave voltammetry under various parameters, including pH, HPMpFP and graphene composition, and scan rate effect. A high electrochemically evaluated surface area using chronoamperometry suggested that the present glucose detection response was intensified. The chronoamperometry results at a work potential of 0.4 V presented a wide linear range of 1 × 10 3 –90 µ M and 88–1 µ M with 0.74 µ M (S/N = 3) as the detection limit. An acceptable recovery has been revealed in the real sample analysis. The electrochemical sensing behaviour of the composite indicates that it may be a promising candidate for a glucose sensor and it significantly extends the range of applications in the electrochemical field.